Proposal for Cut-off Scores for Sensitive Skin on Sensitive Scale-10 in a Group of Adult Women - Cécile Legeas; Laurent Misery; Joachim W. Fluhr; Alain-Claude Roudot; Anne-Sophie Ficheux; Emilie Brenaut (Medical Journals Sweden, 2021)
Sensitive skin is commonly assessed on the basis of self-reports from patients, and sometimes questionnaires, such as the Sensitive Scale-10, are used. The severity of sensitive skin follows a continuum, from the absence of sensitive skin to very sensitive skin. The aims of this cross-sectional study were to compare subjects with and without symptomatic sensitive skin and to propose diagnostic criteria for sensitive skin. A total of 160 women, between 18 and 65 years of age, with and without sensitive skin, and without any associated skin diseases, were recruited. Mean age was 41 years old. Fifty-five percent of participants reported having "very sensitive" or "sensitive" skin. In the sensitive skin group, the participants mainly experienced skin irritability (100%), tautness (97.5%), discomfort (90%) and redness (90%). According to the receiver operating characteristic curve, a Sensitive Scale-10 (SS-10) cut-off value of 12.7 can be used to detect sensitive skin (with a sensitivity of 72.4% and specificity of 90.3%).